충북 영동군의 복합 지질과 지하수 라돈 함량과의 연관성에 대한 고찰 - 문상호(Sang-Ho Moon); 조수영(Soo-Young Cho); 김성현(Sunghyun Kim) (자원환경지질, 2018)
Yeongdong area is located on the border zone between Precambrian Yeongnam massif and central southeastern Ogcheon metamorphic belt, in which Cretaceous Yeongdong sedimentary basin exists. Main geology in this area consists of Precambrian Sobaeksan gneiss complex, Mesozoic igneous and sedimentary rocks and Quaternary alluvial deposits. Above this, age-unknown Ogcheon Supergroup, Paleozoic sedimentary rocks and Tertiary granites also occur in small scale in the northwestern part. This study focuses on the link between the various geology and Rn concentrations in groundwater. For this, twenty wells in alluvial/weathered zone and sixty bedrock aquifer wells were used. Groundwater sampling campaigns were twice run at wet season in August 2015 and dry season in March 2016. Some wells placed in alluvial/weathered part of Precambrian metamorphic rocks and Jurassic granite terrains, as well as Cretaceous porphyry, showed elevated Rn concentrations in groundwater. However, detailed geology showed the distinct feature that these high-Rn groundwaters in metamorphic and granitic terrains are definitely related to proximity of aquifer rocks to Cretaceous porphyry in the study area. The deeper wells placed in bedrock aquifer showed that almost the whole groundwaters in biotite gneiss and schist of Sobaeksan gneiss complex and in Cretaceous sedimentary rocks of Yeongdong basin have low level of Rn concentrations. On the other hand, groundwaters occurring in rock types of granitic gneiss or granite gneiss among Sobaeksan gneiss complex have relatively high Rn concentrations. And also, groundwaters occurring in the border zone between Triassic Cheongsan granites and two-mica granites, and in Jurassic granites neighboring Cretaceous porphyry have relatively high Rn concentrations. Therefore, to get probable and meaningful results for the link between Rn concentrations in groundwater and surrounding geology, quite detailed geology including small-scaled dykes or vein zones should be considered. Furthermore, it is necessary to take account of the spatial proximity of well location to igneous rocks associated with some mineralization/hydrothermal alteration zone rather than in-situ geology itself. 영동지역은 지체구조상 옥천습곡대의 중앙 남동부와 영남육괴와의 경계부에 위치하며, 이들 경계부에는 백악기 영동 퇴적분지가 분포한다. 영동지역의 지질은 주로 선캠브리아시대 소백산 편마암복합체, 중생대 화강암류와 퇴적암류, 그리고 이들 암석을 부정합으로 덮은 제4기 충적층으로 이루어져 있다. 이외에도, 시대미상의 옥천누층군, 고생대의 퇴적암류, 트라이아스기의 화강암류들이 북서측에서 소규모로 산출된다. 이들 다양한 지질에서 산출되는 지하수 내 Rn 함량 특성을 검토하기 위해, 충적층/풍화대 지하수 관정 20개, 암반 지하수 관정 60개를 대상으로 2015년 8월 풍수기와 2016년 3월 갈수기 2 차례에 걸쳐 시료를 채취 분석하였다. 충적/풍화대 지하수의 Rn 함량은 백악기 반암 뿐 아니라 일부 쥬라기 화강암류와 소백산 편마암류 지역에서 높게 나타났다. 그러나, 상세 지질을 살펴보면, 쥬라기 화강암과 흑운모 편마암 자체보다는 인근의 백악기 반암과의 경계부 혹은 반암 인근의 관정 지하수에서 Rn 함량이 높게 나타나는 경향을 볼 수 있다. 암반 지하수에서의 상세 지질별로 Rn 함량 산출 특성을 살펴보면, 영동분지 내 백악기 퇴적암과 소백산 편마암복합체 중 흑운모 편마암과 편암 지역에서 Rn 함량이 적은 편이었고, 백악기 반암 자체, 트라이아스기 청산화강암과 복운모화강암의 경계부위, 쥬라기 화강암과 반암 경계부, 편마암 복합체 중 화강암질 편마암 혹은 화강편마암 지역에서 Rn 함량이 상대적으로 높게 검출되는 것들이 나타났다. 지하수 내 Rn 함량과 지질과의 연관성을 검토할 때, 개략적이고 큰 규모의 지질보다는 맥상 규모로 작은 규모와 이에 따른 정밀한 지질 상황을 고려할 때 지질 및 암종에 따른 Rn 함량의 변화 및 관련성을 의미있게 논의할 수 있을 것으로 판단된다. 또한, 지하수 관정이 위치한 지점에서의 지질 자체보다는 인근에 소규모로 산출되는 맥암, 페그마타이트, 석영맥 등의 산출 및 이들과 관련된 광화대/변질대 등 특수한 지질 상황을 고려한 지하수 수질 특성을 검토할 필요가 있다.